A Genuine Random Sequential Multi-signature Scheme - Yonglong Tang (Institute of Advanced Engineering and Science, 2014)
The usual sequential multi-signature scheme allows the multi-signers to sign the document with their own information and sequence, and the signature is not real random and secure. The paper analyzes the reasons for the insecurity of the previous multi-signature scheme, and puts forward a Genuine Random Sequential Multi-signature Scheme based on The Waters signature scheme, and the experiment proves that this scheme is a good scheme suitable for the practical application with high computing efficiency.